Dengue–SARS-CoV-2 interactions: immune crosstalk, variant emergence, and clinical outcomes - Parra-González, Mariana; Nájera-Maldonado, Lucio; Peralta-Cuevas, Esperanza; Gutierrez-Onofre, Ashley; Jaimes-López, Luis A.; Juarez-Antonio, Juan A.; Degollado-Hernández, Nahomi Y.; Garcia-Atutxa, Igor; Villanueva-Flores, Francisca (Frontiers in Immunology, 2026)
This review aims to provide an overview of dengue–COVID–19 co-infection, emphasizing recently described immunological, genomic, and eco-epidemiological interactions that may influence clinical outcomes and viral evolution. It brings together molecular evidence, immunological perspectives, and epidemiological insights to summarize current hypotheses and working models of these complex disease interactions. We summarize and critically discuss evidence on antibody-dependent enhancement (ADE), cross-reactive immune responses, and cytokine amplification pathways, and propose mechanisms that could underlie exacerbated disease severity. Published clinical data indicate heterogeneity in co-infection outcomes globally, from mild presentations to severe complications, such as hemorrhagic stroke, acute kidney injury, and increased mortality, particularly among populations with prior dengue exposure. Diagnostic complexities arising from serological cross-reactivity underscore the need for simultaneous molecular testing to ensure accurate pathogen identification. Additionally, we review current evidence on reciprocal selective pressures between SARS-CoV-2 variants and dengue serotypes, highlighting potential evolutionary impacts arising from their co-circulation. The available evidence suggests that co-infection may exacerbate inflammatory pathways, lead to increased vascular and organ damage, and complicate patient management. However, definitive clinical evidence for ADE remains inconclusive, underscoring an ongoing need for targeted mechanistic studies. By outlining significant knowledge gaps and summarizing proposed research directions, this review aims to provide a valuable reference for clinicians, immunologists, epidemiologists, and policymakers managing concurrent dengue and COVID-19 outbreaks.